2019
DOI: 10.1177/2333721418823605
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Self-Neglect: A Comparative Study of Indicators and Risk Factors in a Spanish Population

Abstract: Objective: To provide information relevant for detecting potential self-neglecting elders in a Spanish population. Method: This study analyzed the records of 269 social services clients. They were classified in three groups: presumed adequate treatment (AT), at increased risk of abuse (RA), and at increased risk of self-neglect (SN). Social service professionals assessed these cases. Results: Elders at SN presented greater problems in terms of their personal hygiene and appearance, their living conditions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This finding is consistent with another study where older stroke survivors were reported to show a poor state of oral health. 20 There was no significant gender relationship reflected in the oral hygiene of stroke survivors, contrary to findings among healthy individuals where gender was found to be a major determinant of oral hygiene status, with females having the better record. 21 However, a previous study demonstrated that gender was not associated with utilization of oral health services (such as dental visitation) among healthy Nigerian adults.…”
Section: Discussionmentioning
confidence: 60%
“…This finding is consistent with another study where older stroke survivors were reported to show a poor state of oral health. 20 There was no significant gender relationship reflected in the oral hygiene of stroke survivors, contrary to findings among healthy individuals where gender was found to be a major determinant of oral hygiene status, with females having the better record. 21 However, a previous study demonstrated that gender was not associated with utilization of oral health services (such as dental visitation) among healthy Nigerian adults.…”
Section: Discussionmentioning
confidence: 60%
“…Refusing healthcare and social service is a characteristic of self-neglect associated with an increased risk of mortality and damaging one's health and well-being (Dong, 2017). Older adults with self-neglect lack the social support that they need (Touza & Prado, 2019). Additionally, social isolation could be a risk for morbidity and mortality of older adults (Fakoya et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Selfneglect is a chronic and hidden health problem threatening older people's health and safety which has been increasingly on the public radar. Self-neglect has widely been defined as "The inability (intentional or nonintentional) to maintain socially and culturally accepted standards of self-care" [1]. Self-neglect in older adults, or elder self-neglect, is commonly believed to be a behavior profile of an elderly person, manifesting as refusal or failure to provide himself/herself with adequate food, water, clothing, shelter, personal hygiene, medication (when indicated), safety precautions, and financial management [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Elder selfneglect also contributes to poor quality of life and is accompanied by subsequent caregiver neglect, financial exploitation, and multiple forms of elder abuse [9,10]. What is more, self-neglect has a profound impact on the families, neighbors, health-care providers, and surroundings of the elderly [1,11]. For instance, the messy living conditions of elder self-neglecters may attract disease-carrying rats and flies, which potentially presents a public health hazard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation